¡Salud! Southwest Tour - Joanna Mae Mae Souers (Social Medicine Publication Group, 2024)
During this summer of 2009, 12 American medical students from the Escuela Latinoamericana de Medicina (ELAM - Latin American School of Medicine) in Havana, Cuba will board a Recreational Vehicle (RV) to travel across the Southwest region of the United States visiting a number of tribal settlements of American Indian Nations, community colleges and universities. While at the various sites the students will share their personal experiences of what it's like to study at ELAM while promoting the availability of full scholarships for students, volunteer their services while learning about some of the more significant health concerns affecting American Indian populations and to build personal and professional relationships with health care practitioners and members of Native American communities.